Modification of ibuprofen drug release from poly(ethylene glycol) layered silicate nanocomposites prepared by hot‐melt extrusion. Issue 10 (21st December 2013) - Campbell, Kayleen T.; Craig, Duncan Q. M.; McNally, Tony
ABSTRACT Composites of the poorly water soluble drug ibuprofen, a nonsteroidal anti‐inflammatory commonly used for pain relief, with layered silicates (nanoclays) and a poly(ethylene glycol) (PEG) were prepared by hot melt extrusion. A highly intercalated and partially exfoliated morphology was determined using wide‐angle x‐ray diffraction, field emission scanning electron microscopy, and high‐resolution transmission electron microscopy. The crystalline content of PEG was significantly reduced, as shown by differential scanning calorimetry studies, as a consequence of the large surface area of clay platelets physically hindering polymer chain dynamics and, in the case of montmorillonite, by tethering of PEG via hydrogen bonding. Addition of layered silicate retarded the release of ibuprofen from the PEG matrix, even though the crystalline content of PEG was reduced. This study therefore indicates that drug release in solid dispersion systems may be modified or indeed tailored by the inclusion of layered silicates. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40284.